Development of Nectin4/FAP-targeted CAR-T cells secreting IL-7, CCL19, and IL-12 for malignant solid tumors - Li, Fanfan; Zhao, Shuping; Wei, Cheng; Hu, Yaodi; Xu, Tianlong; Xin, Xueyi; Zhu, Tingwei; Shang, Liting; Ke, Shanwen; Zhou, Jiang; Xu, Xiaojun; Gao, Yue; et al. (Frontiers in Immunology, 2022)
Background: Chimeric antigen receptor T (CAR-T) cell therapy has made significant advances for hematological malignancies, but encounters obstacles in the treatment of solid tumors mainly due to tumor immunosuppressive microenvironment. Methods: Immunohistochemistry analysis was performed to examine the cellular expression of nectin cell adhesion molecule-4 (Nectin4) and fibroblast activation protein (FAP) in a variety of malignant solid tumors. Then we engineered the fourth-generation Nectin4-targeted CAR-T (Nectin4-7.19 CAR-T) and FAP-targeted CAR-T (FAP-12 CAR-T) cells to evaluate their safety and efficacy in vitro and in vivo. Results: In our study, we firstly demonstrated the aberrant overexpression of Nectin4 on both primary and metastatic solid tumors and FAP on cancer-associated fibroblasts. Then we found that our fourth-generation Nectin4-7.19 CAR-T cells expressed IL-7 and CCL19 efficiently and exhibited superior proliferation, migration and cytotoxicity than the second-generation Nectin4 CAR-T cells, while FAP-12 CAR-T cells exerted their ability of targeting both murine and human FAP effectively in vitro. In a fully immune-competent mouse model of metastatic colorectal cancer, lymphodepletion pretreated mice achieved complete remission with human Nectin4-targeted murine CAR-T (Nectin4 mCAR-T) cells. And in the NSG mouse model of lung metastases, Nectin4-7.19 CAR-T cells eradicated metastatic tumors and prolonged survival in combination with FAP-12 CAR-T cells. Conclusions: These findings showed that Nectin4-7.19 CAR-T cells had potential therapeutic efficacy and exerted a synergistic role with FAP-12 CAR-T cells, further demonstrating that Nectin4 and FAP were able to serve as promising targets for safe and effective CAR-T therapy of malignant solid tumors.